Fine-Scale Structures in the Mid-Level Eyewall of Super Typhoon Rammasun (2014) Simulated With the WRF-LES Framework - Gao, Zhen; Wu, Liguang; Zhou, Xingyang (Frontiers in Earth Science, 2022)
It has been numerically demonstrated that the turbulence above the boundary is important to tropical cyclone intensification and rapid intensification, but the three-dimensional structures of the sub-grid-scale (SGS) eddy have not been revealed due to the lack of observational data. In this study, two numerical simulations of Super Typhoon Rammasun (2014) were conducted with the Advanced Weather Research and Forecast (WRF) model by incorporating the large-eddy simulation (LES) technique, in which the enhanced eyewall convection and the process of rapid intensification are captured. Consistent with previous observational studies, the strong turbulent kinetic energy (TKE) is found throughout the whole eyewall inside of the radius of maximum wind in both experiments. The simulations indicate that the strong TKE is associated with horizontal rolls with the horizontal extent of 2-4 km, which are aligned azimuthally in the intense eyewall convection. It is indicated that the three-dimensional structures of the SGS eddy can be simulated with the vertical grid spacing of ~100 m when the horizontal grid spacing is 74 m. It is suggested that there is considerable turbulence associated with azimuthally-aligned horizontal rolls in the mid-level eyewall of tropical cyclone.